1992
DOI: 10.2307/2061727
|View full text |Cite
|
Sign up to set email alerts
|

Religion and fertility in the United States: New patterns

Abstract: In the United States, the baby boom-era pattern of high Catholic and low Protestant fertility has ended. Among non-Hispanic whites in the 1980s, Catholic total fertility rates (TFRs) were about one-quarter of a child lower than Protestant rates (1.64 vs. 1.91). Most of the Protestant-Catholic difference is related to later and less frequent marriage among Catholics. Future research on the demography of religious groups should focus on explaining the delayed marriage pattern of Catholics, the high fertility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(94 citation statements)
references
References 22 publications
3
89
0
2
Order By: Relevance
“…Previous country-level studies have found that on average the unaffiliated begin having their children at an older age than the affiliated and have fewer children (Mosher, Williams et al 1992, Skirbekk, Kaufmann et al 2010. Using data aggregated from each country, we estimate that the global 2010−15 Total Fertility Rate (TFR) for unaffiliated women is 1.65 children per woman, nearly a full child less than the rate for religiously affiliated women of 2.59 children per woman.…”
Section: Demographic Characteristics Of the Religiously Unaffiliatedmentioning
confidence: 85%
“…Previous country-level studies have found that on average the unaffiliated begin having their children at an older age than the affiliated and have fewer children (Mosher, Williams et al 1992, Skirbekk, Kaufmann et al 2010. Using data aggregated from each country, we estimate that the global 2010−15 Total Fertility Rate (TFR) for unaffiliated women is 1.65 children per woman, nearly a full child less than the rate for religiously affiliated women of 2.59 children per woman.…”
Section: Demographic Characteristics Of the Religiously Unaffiliatedmentioning
confidence: 85%
“…The contribution of this paper to the theory consists in a quantitative test detecting some mechanisms at play in the data set which are compatible with the alternative hypotheses. Interestingly enough, Mosher, Johnson, and Williams (1992) show that none of these hypotheses fully explain the fertility differential between Catholics and Protestants in the United States. I reach a somewhat identical conclusion for France using quantitative methods and concerning the fertility differences between churchgoing Catholics and others.…”
Section: Detection Of the Theoretical Mechanisms At Playmentioning
confidence: 94%
“…Though not perfectly correlated with denomination, these items reflect religious belief and behavior and are strong predictors of evangelical Protestant affiliation (Layman 2001;Smith 1990;Steensland et al 2000). Unfortunately, the NAES affiliation measure only includes the categories Protestant, (Hout, Greely, and Wilde 2001;Mosher et al 1992) when exploring 11 fertility differences among American Christians. To test the hypothesis that the beliefs and messages that may mobilize conservative women politically are encouraging higher fertility rates, it is important to determine whether religious traditionalists are having more children than their peers, which is a slightly different measure than previously used in the literature.…”
Section: Hypotheses and Methodsmentioning
confidence: 99%
“…Traditionally, most fertility studies involving religious influence have addressed the differences between Catholics and Protestants, as Catholics tended to have larger families; but currently, this gap is almost nonexistent due to later marriage by Catholics (resulting in fewer children) and larger families of Protestants who attend church frequently (Lehrer 2004;McQuillan 2004;Mosher, Williams and Johnson 1992). More recent studies focus on the fertility differentials between mainline and evangelical Protestants, mostly attributed to doctrinal 5 differences of evangelicals espousing stronger pronatalist views (be fruitful and multiply) and an aversion to contraceptives and abortion (playing God) (Marcum 1981;McQuillan 2004).…”
Section: The Social Capital Of Children and Religionmentioning
confidence: 99%
See 1 more Smart Citation